Interleukin inhibitors for psoriatic arthritis - Sharma, Gaurav (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To evaluate benefits and harms of interleukin inhibitors for the treatment of psoriatic arthritis (PsA).